Copyright of artificial intelligence autonomous production: some reflections around the concepts of mind and intelligence (BioLaw Journal - Rivista di BioDiritto, 2019)
The research problem of the present article consists of two questions: can an Artificial Intelligence (IA) be considered an author? Who owns the copyrighted material produced by IA? The first topic gives a brief deductive and theoretical approach to the ontology of mind and artificial intelligence. Subsequently, the compatibility between these guidelines for the legal concept of author contained in some Copyright Laws. In the end, it is proposed the ontological impossibility of an AI holds intellectual property rights, even if derived from autonomous acts, attributing them to its programmer/creator.
Keywords: Artificial intelligence; copyright; intellectual property